Approaches to technique and technical training in the high jump - Ritzdorf, W. (New Studies in Athletics, 2009)
The coach's approach to technique and technical preparation are critical for his/her athlete's success. All coaches face this challenge, regardless of the athlete's level of ability or performance. The author, who has coached two Olympic champions as well as a number of other top-class high jumpers and is currently the Director of the IAAF World High Jump Centre in Cologne, Germany, starts with a discussion of the importance of understanding the technical model in his event. He then describes the key elements of the approach he has developed while working with athletes who are normally quite talented but may be under-developed from a training or technical point of view. It includes two strategies for technique development: a) checking whether the athlete's personal style contributes to performance or hinders the achievement of key technical elements and b) developing the athlete's technical model based on an assessment of his/her reactive strength, which is the most important factor affecting the take-off in the high jump. He then gives a brief description of the four elements of the technical preparation programme he uses: a) development of general qualities, b) development of specific qualities, c) development of specific skills and d) technical training.